Effectiveness of Transthoracic Hybrid Minimally Invasive Esophagectomy: A Meta-Analysis - Zheng-Dao Wei; Han-Lu Zhang; Yu-Shang Yang; Long-Qi Chen (Journal of Investigative Surgery, 2021)
Background Transthoracic hybrid minimally invasive esophagectomy (HMIE) is frequently performed in patients with esophageal cancer. However, no conclusive benefit has been defined for HMIE compared with open esophagectomy (OE) or totally MIE (TMIE). The aim of this meta-analysis is to evaluate the effectiveness of HMIE compared with OE and TMIE. Methods PubMed, Embase (via OVID) and Cochrane databases were comprehensively searched for relevant studies up to January 2019. Studies comparing the efficacy of transthoracic HMIE with OE or TMIE were included in this meta-analysis. Results Twenty-nine relevant studies comprising 3994 patients were identified and included in the analysis of HMIE vs OE. HMIE decreased the incidence of postoperative total morbidity (OR = 0.66, 95% CI 0.55 to 0.80, p = 0.00), pneumonia (OR = 0.55, 95% CI 0.45 to 0.66, p = 0.00), in-hospital mortality (OR = 0.54, 95% CI 0.36 to 0.83, p = 0.01), duration of hospitalization (SMD=-1.03, 95% CI -1.73 to -0.33, p = 0.00) and the estimated intraoperative blood loss (SMD=-1.01, 95% CI -1.62 to -0.40, p = 0.00) compared with OE. Twenty-one relevant studies comprising 3007 patients were identified and included in the analysis of HMIE vs TMIE. HMIE increased estimated intraoperative blood loss [standardized mean difference (SMD) = 1.02, 95% CI 0.45 to 1.58, p = 0.00] and the incidence of postoperative pneumonia (OR = 1.69, 95% CI 1.26 to 2.26, p = 0.00) compared with TMIE. No statistical differences were observed for other surgical outcomes. Conclusions In our opinion, HMIE is a promising surgical technique. But further RCTs are still needed to confirm the advantages and disadvantages of HMIE mentioned above.